The genomic portrait of the Picene culture provides new insights into the Italic Iron Age and the legacy of the Roman Empire in Central Italy - Francesco Ravasini; Helja Kabral; Anu Solnik; Luciana de Gennaro; Francesco Montinaro; Ruoyun Hui; Chiara Delpino; Stefano Finocchi; Pierluigi Giroldini; Oscar Mei; Michael Allen Beck De Lotto; Elisabetta Cilli; et al. (Genome Biology)
Abstract Background The Italic Iron Age is characterized by the presence of various ethnic groups partially examined from a genomic perspective. To explore the evolution of Iron Age Italic populations and the genetic impact of Romanization, we focus on the Picenes, one of the most fascinating pre-Roman civilizations, who flourished on the Middle Adriatic side of Central Italy between the 9th and the 3rd century BCE, until the Roman colonization. Results More than 50 samples are reported, spanning more than 1000 years of history from the Iron Age to Late Antiquity. Despite cultural diversity, our analysis reveals no major differences between the Picenes and other coeval populations, suggesting a shared genetic history of the Central Italian Iron Age ethnic groups. Nevertheless, a slight genetic differentiation between populations along the Adriatic and Tyrrhenian coasts can be observed, possibly due to different population dynamics in the two sides of Italy and/or genetic contacts across the Adriatic Sea. Additionally, we identify several individuals with ancestries deviating from their general population. Lastly, in our Late Antiquity site, we observe a drastic change in the genetic landscape of the Middle Adriatic region, indicating a relevant influx from the Near East, possibly as a consequence of Romanization. Conclusions Our findings, consistently with archeological hypotheses, suggest genetic interactions across the Adriatic Sea during the Bronze/Iron Age and a high level of individual mobility typical of cosmopolitan societies. Finally, we highlight the role of the Roman Empire in shaping genetic and phenotypic changes that greatly impact the Italian peninsula.